建构中国想像共同体的电影企业家 ：日战前新加坡《南洋商报》的中国电影广告初探 Construction of China’s imagined community by cinema entrepreneurs in pre-war Singapore : a preliminary study of Chinese movie advertisements in Nanyang Siang Pau - 杨婉欣 Yowendra, Sinta (2016)
30年代起，已有许多华人电影企业家把中国电影发行权带到新马，透过电影消费文化拉近华侨与祖国的距离。逢中日战争，南洋华侨见证了前所未有的民族主义高涨，报纸、电影等媒介是宣传爱国讯息与赚取利益的双重途径，难分辨的爱国意识与商业驱动力成了当时文化企业的特点。若商家发行的影片带有爱国意识，广告宣传文字不免充满爱国讯息，时而也写明把影片放映的部分收入捐给中国难民。因此，看电影也成了爱国举动，消费文化与民族主义紧密相连。这种营销方式亦成为建构中国想像共同体的途径，使遍布世界各地的华侨看似统一的中华民族。本文将集中探讨二战前新加坡电影业的华人电影企业家如何通过广告的营销方式，把中国想像共同体强加于实为分裂群体的离散华人。广告文本中所再现的民族主义非绝对统一，而是异质的，包括：对国民政府的忠诚、共产党的推崇、中国古代的文化认同、与中国同胞的联系等。为了进一步分析当时的文化环境，本文将分析新加坡《南洋商报》电影广告为主轴，以上海《申报》所刊登的相同电影广告为辅来作比较，从而结合电影企业家的华人性与电影广告的意识形态来进行探究。While Hollywood movies predominated the cinemas in 1930s Singapore, there were still several Chinese cinema entrepreneurs who distributed movies imported from China. The profitable consumer culture based on Chinese movies bridged the gap between overseas Chinese and their motherland. Film distribution companies employed patriotism in their advertising strategies, constructing an imagined unified nation comprising of the Chinese scattered worldwide. Undeniably, an unprecedented surge of nationalism was witnessed during the Sino-Japanese War. Mass media such as newspaper, journals and movies became a lucrative platform to disseminate patriotic messages, blurring the line between the nationalism and capitalistic motivation of this commerce. As a result, such ambiguity became the characteristic of the Chinese cultural enterprise worldwide. Often, the consumer behavior of watching Chinese movies is portrayed as a patriotic act. Movies with nationalistic content were advertised with strong patriotic messages, sometimes appealing to Chinese community by donation of screening profits to China refugees. In this essay, I examine how Chinese cinema entrepreneurs in Singapore impose an imaginary coherence on the segregated Chinese diasporic community through their advertising strategies. As local cinema production was still in its preliminary stage, advertisements published in Singapore’s Nanyang Siang Pau are the main focus in this essay. I address this topic through re-examining the representations of nationalism, which varies from loyalty to Kuomintang, saluting the Chinese Communist Party, identifying with ancient Chinese legend and connecting with their compatriots in China. I propose that the nationalism presented in these advertisements – instead of being absolutely coherent – were heterogeneous in nature. To delve deeper, I also use advertisements in Shanghai’s Shun Pao as a supplement to compare the cultural atmosphere between the two cities, concurrently exploring the Chineseness of cinema entrepreneurs and the ideologies conveyed in the advertisements.